Comprehensive Evaluation of Moisture and Dew Point Characteristics of SF₆ Gas in 150 kV GIS Circuit Breakers: Operational Insights from Krembangan Substation (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Sulfur Hexafluoride (SF₆) gas is widely used as an insulating and arc-quenching medium in Gas Insulated Substations (GIS), particularly in high-voltage equipment such as Power Circuit Breakers. The performance and reliability of SF₆ gas are strongly influenced by two key parameters: moisture content and dew point. Excessive moisture can reduce the dielectric strength of the gas, increase the risk of internal flashovers, and ultimately lead to equipment failure. This study aims to analyze the moisture content and dew point values of SF₆ gas in circuit breakers installed at the 150 kV GIS in Krembangan Substation. The analysis evaluates whether these parameters remain within acceptable limits according to international standards specifically CIGRE Technical Brochure No. 234 and IEEE Std. 1125. The method involved collecting test data using an SF₆ gas analyzer, followed by standardization calculations to assess gas quality. The results show that all measured moisture content values are well below the factory maximum limit of 500 ppmv and also comply with the calculated thresholds of CIGRE standards. Likewise, the dew point measurements fall within the factory-recommended range of -20°C to -30°C. After applying standard conversion calculations, the dew point results still meet CIGRE guidelines, remaining above the critical value of -5°C. These findings indicate that the SF₆ gas in all five PMTs at GIS 150 kV Krembangan remains in good condition and continues to meet international reliability and safety standards.